European internet early warning system. (18th March 2009) - Hesse, Malte; Pohlmann, Norbert
The internet is consisting of autonomous systems each managed by individual and mostly rival organisations. This situation makes it very difficult to capture the state of the internet as a whole. An individual internet situation awareness for various stakeholders can be accomplished by creating a common basis for private and public operators to monitor their networks, by offering them a common smart approach to monitor their network individually and the additional benefit of participating to establish a global view, which they can use as a reference for their local situation. This smart approach should utilise well-proven existing global statistics, best practices and existing technical sensors, which can be adapted to the overall common framework. From this, output for all relevant stakeholders can be generated to fulfil the individual needs. Once the internet situation awareness is accomplished, it can be used besides others for an European internet early warning system.